Human Cytomegalovirus pUS27 G Protein-Coupled Receptor Homologue Is Required for Efficient Spread by the Extracellular Route but Not for Direct Cell-to-Cell Spread - O'Connor, Christine M. (American Society for Microbiology, 2011)

(untitled)
Human cytomegalovirus (HCMV) encodes multiple G protein-coupled receptor (GPCR) homologues, including pUS27, pUS28, pUL33, and pUL78. To explore the function of pUS27, we constructed pUS27-deficient derivates of two clinical isolates of HCMV. BFX-GFPstopUS27 is a FIX variant with a single base pair change in the US27 open reading frame, generating a stop codon that ablates accumulation of the GPCR homologue, and TB40/E-mCherrydlUS27 lacks the entire US27 coding region. BFX-GFPstopUS27 generated 10-fold less extracellular progeny in fibroblasts, and TB40/E-mCherrydlUS27 exhibited a similar defect in endothelial cells. The pUS27-deficient FIX derivative produced normal quantities of viral DNA and viral proteins tested, and a late virion protein was appropriately localized to the cytoplasmic assembly zone. After infection at a low multiplicity with wild-type FIX virus, neutralizing antibody reduced the accumulation of intracellular viral DNA and intracellular virions, as would be expected if the virus is limited to direct cell-to-cell spread by neutralization of extracellular virus. In contrast, the antibody had little effect on the spread of the BFX-GFPstopUS27 virus. Further, after infection at a low multiplicity, the pUS27-deficient TB40/E virus exhibited a growth defect in endothelial cells, where the clinical isolate normally generates extracellular virus, but the TB40/E derivative exhibited little defect in epithelial cells, where the wild-type virus does not produce extracellular virus. Thus, mutants lacking pUS27 rely primarily on direct cell-to-cell spread, and we conclude that the viral GCPR homologue acts at a late stage of the HCMV replication cycle to support spread of virus by the extracellular route.